Disassembly and trimer formation of E2 protein cage : the effects of C-terminus, salt, and protonation state - Lee, Hwankyu (2020)
E2 protein cages, which consist of the assembled 60 subunits, were simulated at two levels of protonation to mimic their electrostatic properties at pH 4 and 7 using all-atom models. Starting with the initial configuration of the assembled 60-mer, either the truncation of C-terminus or the protonation state of pH 4 induces the disassembly of 60-mer, leading to the formation of trimers. Hydrodynamic radii (R h) of E2 monomer, trimer, and 60-mer are calculated from diffusivities, which agree well with experimental values. R h become smaller for the disassembled E2, confirming the formation of clusters smaller than 60-mer. Anionic Asp419 and Glu421 at the C-terminus interact with Lys240 of a neighboring trimer, while hydrophobic Leu424 and Met425 at the C-terminus interact with Pro313∼Ala318 of a neighboring trimer. When anionic residues of E2 60-mer are protonated (neutralized), the assembled 60-mer are stabilized by hydrophobic interactions of C-terminus. These indicate that the stability of E2 60-mer is attributed to both electrostatic and hydrophobic inter-trimer interactions of the neighboring C-termini. These findings support the experimental interpretation regarding the formation of trimer as an intermediate between E2 monomer and 60-mer, and help explain the key role of C-terminus for electrostatic and hydrophobic inter-trimer interactions.